Images of Women in the Selected Novels of Gabriel Garcia Marquez - Billanes, Lorna Arejola (Review of Women's Studies; Vol 14 No 1 (2004): Review of Women's Studies Volume XIV, Number 1 (January-June 2004), 2004)
This paper is a preliminary attempt to explore Gabriel Garcia Marquez' treatment of women in his writing, drawing only a broad outline by extracting the main patterns of his novels - their movement, problems and trends, in order to illustrate how he has embedded in his narrative his worldview on women, particularly as he has employed them as literary characters.